Author Correction: Signal quality of simultaneously recorded endovascular, subdural and epidural signals are comparable. Issue 1 (December 2018) - John, Sam; Opie, Nicholas; Wong, Yan; Rind, Gil; Ronayne, Stephen; Gerboni, Giulia; Bauquier, Sebastien; O'Brien, Terence; May, Clive; Grayden, David; Oxley, Thomas
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.